Perbandingan pengaruh latihan ladder drills in out dan ickey shuffle terhadap kecepatan dan kelincahan - Fatchurrahman, Faried; Sudijandoko, Andun; Widodo, Achmad (Universitas Nusantara PGRI Kediri, 2019)
The purpose of this study was to analyze the comparison of the effect of ladder drills in out training and ladder drills ickey shuffle exercises on increasing speed and agility in students of futsal extracurricular activities at SMA 1 Krian. The method used in this research is quantitative descriptive method with a quasi-experimental method. The population in this study were all students who participated in futsal extracurricular activities of SMAN 1 Krian with the number of the subject of 30 students. The design of this study uses only matching design with data analysis using ANOVA. The results showed that the ladder drills in out exercise significantly affected the increase in speed and agility and the ladder drills ickey shuffle exercise had a significant effect on increasing speed and agility. The conclusion of this study was that the ladder drill in out and the ickey shuffle significantly influence speed and agility.